2014
DOI: 10.1002/asi.23011
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a scatter/gather interface for supporting distinct health information search tasks

Abstract: Web search engines are important gateways for users to access health information. This study explored whether a search interface based on the Bing API and enabled by Scatter/Gather, a well-known document-clustering technique, can improve health information searches. Forty participants without medical backgrounds were randomly assigned to two interfaces: a baseline interface that resembles typical web search engines and a Scatter/Gather interface. Both groups performed two lookup and two exploratory health-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
(63 reference statements)
0
13
0
Order By: Relevance
“…These data were recorded in transaction logs. The analysis of query reformulation followed the topology developed by Rieh and Xie [ 44 ] and modified by Zhang et al [ 45 ]. The resulting topology included five types of query reformulations based on semantic changes: (1) specification (participants specify the meaning of the previous query), (2) generalization (participants generalize the meaning of the previous query), (3) parallel movement (participants replace one concept in the previous query with a new concept and the two queries have a partial overlap in meaning), (4) new concept movement (participants change to new concepts and the new query does not overlap with the previous query), and (5) rephrasing (participants rephrase the previous query by changing the form of the query without changing the meaning, such as correcting misspellings and rephrasing the previous query into a question).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data were recorded in transaction logs. The analysis of query reformulation followed the topology developed by Rieh and Xie [ 44 ] and modified by Zhang et al [ 45 ]. The resulting topology included five types of query reformulations based on semantic changes: (1) specification (participants specify the meaning of the previous query), (2) generalization (participants generalize the meaning of the previous query), (3) parallel movement (participants replace one concept in the previous query with a new concept and the two queries have a partial overlap in meaning), (4) new concept movement (participants change to new concepts and the new query does not overlap with the previous query), and (5) rephrasing (participants rephrase the previous query by changing the form of the query without changing the meaning, such as correcting misspellings and rephrasing the previous query into a question).…”
Section: Methodsmentioning
confidence: 99%
“…A series of t tests suggests that the two interface groups did not differ in demographics (including age, gender, computer experience, and health information search experience), nor in any of the measurements on search behavior, perceptions of tasks, and experience with search systems [ 45 ]. In addition, two-way ANOVAs (analyses of variance) suggested that there were no significant interactions between interfaces and information preferences (as measured by KHOS-I).…”
Section: Methodsmentioning
confidence: 99%
“…Two independent coders coded all the query reformulation instances and the intercoder reliability was 98.5%. The preliminary data analyses suggested that the two interface groups did not differ in demographics (including age, gender, computer experience, and health information search experience), nor in any of the behavioral measurements (including session length, number of query submitted, conceptual changes in query reformulation, and sites visited) (Zhang, Broussard, Ke, & Gong, 2013). Because the focus on the current paper is participants' behavior and cognitive activities while searching for treatment options for migraines, the groups that used two separate interfaces were pooled together.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of faunal communities depends on the interaction of physical and biological factors. Different insect assemblages in a stream are profoundly influenced by noble metals and physical factors such as current velocity, dissolved oxygen, temperature, and water conductivity (Bilton et al, 2001;Zhang et al, 2014;Free et al, 2009;Cai et al, 2017a)…”
Section: Introductionmentioning
confidence: 99%